Green Sukuk: leveraging Islamic finance for ecological sustainability - Ali, Mohammad Mahbubi; Rusydiana, Aam Slamet; As-Salafiyah, Aisyah; Mah Abdullah, Shahino (Routledge (Taylor & Francis Group), 2026)
Green sukuk as a Shari’ah-compliant financial instrument has emerged as an important mechanism to finance sustainable projects that are environmentally friendly and adhere to Islamic ethical principles. This study explores the Islamic perspective on green sukuk, emphasizing its alignment with the objectives of Shari’ah (maqasid al-Shari’ah) in supporting environmental management and ecological sustainability. In addition, this study examines various green sukuk structures, including Murabahah, Istisna’, and Wakalah, demonstrating their adaptability to various financing needs. By analysing the relationship between Islamic values and green finance, this study highlights the role of green sukuk in addressing global environmental challenges, particularly in Malaysia and Indonesia. With a positive trajectory, green sukuk issuance has the potential to continue. This study also identifies key challenges, such as the absence of a standardized green taxonomy, limited secondary market, and high compliance costs associated with certification and reporting. To address these challenges, this study proposes specific policy recommendations, such as regulatory harmonization, capacity building, and alignment with global sustainability frameworks such as the Sustainable Development Goals (SDGs). The findings of this study indicate that green sukuk provide an innovative and ethical solution to finance sustainable development while strengthening the principles of Islamic finance.